Tren Global Penelitian Pendidikan Cardiopulmonary Resuscitation (CPR) Pada Mahasiswa dan Pelajar: Analisis Bibliometrik - Dea Salamiah; Azizah Khoiriyati (Malahayati Nursing Journal, 2026)
ABSTRACT Cardiopulmonary resuscitation (CPR) education for university students is an important strategy to increase bystander CPR rates and reduce mortality due to cardiac arrest. As global attention to CPR education increases, the number of scientific publications in this field continues to grow. However, comprehensive mapping of research developments through bibliometric analysis is still limited. This study aims to analyze trends, characteristics, and research focus on CPR education for university students using a bibliometric approach. Bibliometric analysis was conducted on articles indexed in the Scopus database for the period 2015–2025. The search used keywords (TITLE-ABS-KEY (cpr) AND TITLE-ABS-KEY (student)) with limitations on the fields of medicine and nursing, article document type, and English language. A total of 529 articles that met the inclusion criteria were analyzed using Scopus, MapChart, and VOSviewer to map publication trends, country distribution, and research keyword networks. The number of publications showed a significant increase after 2017. Research contributions were dominated by developed countries, particularly the United States and European countries, while participation from developing countries was still limited. Keyword analysis identified a research focus on CPR training, students, and education, as well as the development of innovative learning methods such as simulation, serious games, and virtual reality. Research on CPR education for university students and pupils continues to grow, with a trend toward technology-based learning approaches. Further research opportunities are open in the context of developing countries and on aspects of the implementation and sustainability of CPR competencies.  Keywords: CPR Training, Students, Medical Education.  ABSTRAK Pendidikan cardiopulmonary resuscitation (CPR) pada mahasiswa dan pelajar merupakan strategi penting untuk meningkatkan angka bystander CPR serta menurunkan mortalitas akibat henti jantung. Seiring meningkatnya perhatian global terhadap edukasi CPR, jumlah publikasi ilmiah di bidang ini terus berkembang. Namun, pemetaan perkembangan penelitian secara komprehensif melalui analisis bibliometrik masih terbatas. Penelitian ini bertujuan untuk menganalisis tren, karakteristik, dan fokus penelitian mengenai pendidikan CPR pada mahasiswa dan pelajar menggunakan pendekatan bibliometrik. Analisis bibliometrik dilakukan terhadap artikel yang terindeks dalam basis data Scopus pada periode 2015–2025. Pencarian menggunakan kata kunci (TITLE-ABS-KEY (cpr) AND TITLE-ABS-KEY (student)) dengan pembatasan bidang ilmu medicine dan nursing, jenis dokumen artikel, serta bahasa Inggris. Sebanyak 529 artikel yang memenuhi kriteria inklusi dianalisis menggunakan Scopus, MapChart, dan VOSviewer untuk memetakan tren publikasi, distribusi negara, serta jaringan kata kunci penelitian. Jumlah publikasi menunjukkan peningkatan signifikan setelah tahun 2017. Kontribusi penelitian didominasi oleh negara maju, terutama Amerika Serikat dan negara-negara Eropa, sementara partisipasi negara berkembang masih terbatas. Analisis kata kunci mengidentifikasi fokus penelitian pada CPR training, students, dan education, serta perkembangan metode pembelajaran inovatif seperti simulasi, serious games, dan virtual reality. Penelitian mengenai pendidikan CPR pada mahasiswa dan pelajar terus berkembang dengan kecenderungan menuju pendekatan pembelajaran berbasis teknologi. Peluang penelitian selanjutnya terbuka pada konteks negara berkembang serta pada aspek implementasi dan keberlanjutan kompetensi CPR. Kata Kunci: CPR Training, Students, Medical Education.